A study on the causes of the weak performance among the ex Alamanda students: Finding ways for academic improvement / Hasnizawati Hashim, Rozieana A. Halid @Khalid and Wan Kalthom Yahya - Hashim, Hasnizawati; A. Halid @Khalid, Rozieana; Yahya, Wan Kalthom (2010)
In July 2010, Faculty of Business Management received more than 500 students from Alamanda Campus. It has contributed to the rising number of the existing faculty students which has reached approximately 1500. The current academic performances of these students indicate that 40% of them obtain CGPA below 2.30. This figure indirectly contributes to the statistics of the students under PI and P2 status. Concomitantly, this portrays the overall poor performance for Business Faculty. Even though the faculty "Kudup Akan Berkembang" Program (hereinafter KAB) could be one the ways to help them to be on track again in their studies, it is not a hundred percent guaranteed without knowing the root causes of the problem. In order to understand why the students are weak in their performance, a study is conducted and aimed at understanding what are the factors that contribute to this poor performance and how to improve the situation. Some suggestions will be given at the end of the discussion to be implemented by the PDCA (Plan, Do, Check and Act) faculty committee. It is hoped that with the analysis and the suggestion proposed, the students would be able to upgrade their academic performance and increase their inner drive to keep on improving as well.